The expression and localization of estrogen receptor beta in hyperplastic and neoplastic prostate lesions - Fejsa Levakov, Aleksandra; Mocko Kaćanski, Mihaela; Vučković, Nada; Živojinov, Mirjana; Amidžić, Jelena; Ilić Sabo, Jelena (Vojnosanitetski pregled, 2015)
Background/Aim. Benign acini in benign prostatic hyperplasia (BPH) are lined with pseudostratified cylindrical epithelium with a continuous basal cell layer. Adenocarcinoma of the prostate is the most common cancer in men. High gradus-prostatic intraepithelial neoplasia (HGPIN) lesions precede invasive cancer. Prostate adenocarcinoma (PCa) implies a complete absence of basal cells and stromal invasion by malignant acini. Estrogen receptor (ER) is located in nuclei of acinar basal and secretory cells and partially in stromal cells. The aim of this research was to demonstrate and localize ER in BPH and in PCa of different Gleason scores. Considering literature data for ER-beta expression in different morphologic prostate lesions, it is assumed that there is expression of ER-beta in most moderately differentiated PCa, and that the observed receptor expression is lost with increasing of the Gleason score. Methods. Four groups of patients were formed: the control with BPH and three experimental groups with PCa of different grades and scores, according to the Gleason grading system. The patients were male of various ages suspected of PCa, based on clinical and laboratory parameters. The study was conducted in a period 2010–2012. None of the patients received prior hormonal therapy. Sextant byopsies with BPH and PCa were treated for ER-beta (Novocastra). Localization and intensity of ER-beta expression is reported through the score: 0 = zero; 1 = < 1%; 2 = 1–10%; 3 = 11–33%; 4 = 34–66%; 5 – > 66%. Positive fibroblasts and endothelial cells are used for comparison. Results. ER-beta expression in acinar epithelial cells was the weakest in well-differentiated adenocarcinoma. A decline of ER-beta expression was noticed in malignant lesions of the prostate vs benign ones. Less differentiated adenocarcinomas showed a decrease of ER-beta expression in basal and in the secretory cells. ER-beta expression in basal cells was stronger than in secretory ones in BPH and well-differentiated adenocarcinoma. Conclusion. ER-beta expression was most pronounced in BHP samples and declined in malignant prostatic lesions. This finding supports statement on antiproliferative role of ER-beta in prostatic tissue.